Creating a Positive Environment in Your Academic Division - Frances C. Welch (Academic Chairpersons Conference Proceedings, 2016)
During this panel discussion, a dean, associate dean, and two department chairs will discuss how to “create a positive working environment.” Based on their collective experience, panel members will discuss best practices when (1) building relationships; (2) using backward planning; (3) mentoring new faculty members; and (3) communicating effectively.
Keywords: Building Relationships; planning; mentoring; communicating